Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Improving sightings-derived residency estimation for whale shark aggregations: A novel metric applied to a global data set - Gonzalo Araujo; Ariana Agustines; Steffen S. Bach; Jesse E. M. Cochran; Emilio de la Parra-Galván; Rafael de la Parra-Venegas; Stella Diamant; Alistair Dove; Steve Fox; Rachel T. Graham; Sofia M. Green; Jonathan R. Green; et al. (Frontiers in Marine Science, 2022)
The world’s largest extant fish, the whale shark Rhincodon typus , is one of the most-studied species of sharks globally. The discovery of predictable aggregation sites where these animals gather seasonally or are sighted year-round – most of which are coastal and juvenile-dominated – has allowed for a rapid expansion of research on this species. The most common method for studying whale sharks at these sites is photographic identification (photo-ID). This technique allows for long-term individual-based data to be collected which can, in turn, be used to evaluate population structure, build population models, identify long-distance movements, and assess philopatry and other population dynamics. Lagged identification rate (LIR) models have fewer underlying assumptions than more traditional capture mark recapture approaches, making them more broadly applicable to marine taxa, especially far-ranging megafauna species like whale sharks. However, the increased flexibility comes at a cost. Parameter estimations based on LIR can be difficult to interpret and may not be comparable between areas with different sampling regimes. Using a unique data-set from the Philippines with ~8 years of nearly continuous survey effort, we were able to derive a metric for converting LIR residency estimates into more intuitive days-per-year units. We applied this metric to 25 different sites allowing for the first quantitatively-meaningful comparison of sightings-derived residence among the world’s whale shark aggregations. We validated these results against the only three published acoustic residence metrics (falling within the ranges established by these earlier works in all cases). The results were then used to understand residency behaviours exhibited by the sharks at each site. The adjusted residency metric is an improvement to LIR-based population modelling, already one of the most widely used tools for describing whale shark aggregations. The standardised methods presented here can serve as a valuable tool for assessing residency patterns of whale sharks, which is crucial for tailored conservation action, and can cautiously be tested in other taxa.

A review of the biology, fisheries and conservation of the whale shark Rhincodon typus - D. Rowat; K. S. Brooks (Journal of Fish Biology, 2012)
Although the whale shark Rhincodon typus is the largest extant fish, it was not described until 1828 and by 1986 there were only 320 records of this species. Since then, growth in tourism and marine recreation globally has lead to a significant increase in the number of sightings and several areas with annual occurrences have been identified, spurring a surge of research on the species. Simultaneously, there was a great expansion in targeted R. typus fisheries to supply the Asian restaurant trade, as well as a largely un‐quantified by‐catch of the species in purse‐seine tuna fisheries. Currently R. typus is listed by the IUCN as vulnerable, due mainly to the effects of targeted fishing in two areas. Photo‐identification has shown that R. typus form seasonal size and sex segregated feeding aggregations and that a large proportion of fish in these aggregations are philopatric in the broadest sense, tending to return to, or remain near, a particular site. Somewhat conversely, satellite tracking studies have shown that fish from these aggregations can migrate at ocean‐basin scales and genetic studies have, to date, found little graphic differentiation globally. Conservation approaches are now informed by observational and environmental studies that have provided insight into the feeding habits of the species and its preferred habitats. Notwithstanding these advances, there remain notable gaps in the knowledge of this species particularly with respect to the life history of neonates and adults who are not found in the feeding aggregations.

New records of neonatal and juvenile whale sharks (Rhincodon typus) from the Indian Ocean - D. Rowat; M. A. Gore; B. B. Baloch; Z. Islam; E. Ahmad; Q. M. Ali; R. M. Culloch; S. Hameed; S. A. Hasnain; B. Hussain; S. Kiani; J. Siddiqui; et al. (Environmental Biology of Fishes, 2008)

Scarring patterns and relative mortality rates of Indian Ocean whale sharks - C. W. Speed; M. G. Meekan; D. Rowat; S. J. Pierce; A. D. Marshall; C. J. A. Bradshaw (Journal of Fish Biology, 2008)
This study recorded the scarring rate and severity for whale sharks Rhincodon typus from three Indian Ocean aggregations (Australia, Seychelles and Mozambique), and examined whether scarring (mostly attributed to boat strikes and predator attacks) influences apparent survival rates using photo‐identification libraries. Identifications were based on spot‐and‐stripe patterns that are unique to individual whale sharks. Scarring was most prevalent in the Seychelles aggregation (67% of individuals). Predator bites were the most frequent source of scarring (aside from minor nicks and abrasions) and 27% of individuals had scars consistent with predator attacks. A similar proportion of whale sharks had blunt trauma, laceration and amputation scars, the majority of which appeared to be caused by ship collisions. Predator bites were more common (44% of individuals) and scars from ship collisions were less common at Ningaloo Reef than at the other two locations (probability of among‐site differences occurring randomly = 0·0007 based on a randomized multinomial contingency analysis). In all aggregations, scars occurred most often on the caudal fin, which may result from the fin being the body part closest to the surface when boats pass over, or they may provide a large target for predator attack. No evidence was found for an effect of scarring on apparent survival ( φ ; mean ± s . e .) for the Ningaloo (not scarred φ = 0·858 ± 0·033; scarred φ = 0·929 ± 0·033) or Seychelles populations (not scarred φ = 0·502 ± 0·060; scarred φ = 0·538 ± 0·070). The lower apparent survival of the Seychelles population may be attributed to a high number of transient whale sharks in this aggregation that might bias estimates. This study indicates that while scarring from natural predators and smaller vessels appears to be unrelated to whale shark survival, the effect of deaths related to ship strike need to be quantified to assist in future management of this species.

Aggregations of juvenile whale sharks (Rhincodon typus) in the Gulf of Tadjoura, Djibouti - D. Rowat; M. G. Meekan; U. Engelhardt; B. Pardigon; M. Vely (Environmental Biology of Fishes, 2007)